Non‐nucleoside reverse transcriptase inhibitors: a review on pharmacokinetics, pharmacodynamics, safety and tolerability. Issue 1 (4th September 2013) - Usach, Iris; Melis, Virginia; Peris, José‐Esteban
Abstract : Introduction: Human immunodeficiency virus (HIV) type‐1 non‐nucleoside and nucleoside reverse transcriptase inhibitors (NNRTIs) are key drugs of highly active antiretroviral therapy (HAART) in the clinical management of acquired immune deficiency syndrome (AIDS)/HIV infection. Discussion: First‐generation NNRTIs, nevirapine (NVP), delavirdine (DLV) and efavirenz (EFV) are drugs with a low genetic barrier and poor resistance profile, which has led to the development of new generations of NNRTIs. Second‐generation NNRTIs, etravirine (ETR) and rilpivirine (RPV) have been approved by the Food and Drug Administration and European Union, and the next generation of drugs is currently being clinically developed. This review describes recent clinical data, pharmacokinetics, metabolism, pharmacodynamics, safety and tolerability of commercialized NNRTIs, including the effects of sex, race and age differences on pharmacokinetics and safety. Moreover, it summarizes the characteristics of next‐generation NNRTIs: lersivirine, GSK 2248761, RDEA806, BILR 355 BS, calanolide A, MK‐4965, MK‐1439 and MK‐6186. Conclusions: This review presents a wide description of NNRTIs, providing useful information for researchers interested in this field, both in clinical use and in research.